N `-[1-(5-Bromo-2-hydroxyphenyl)ethylidene]-3,4,5-trihydroxybenzohydrazi de dimethyl sulfoxide solvate trihydrate - Gwaram, N.S.; Khaledi, H.; Ali, H.M.; Robinson, W.T.; Abdulla, M.A. (International Union of Crystallography, 2010)
The benzohydrazide molecule in the title compound, C15H13BrN2O5 center dot C2H6OS center dot 3H(2)O, is almost planar with an r.m.s. deviation for the non-H atoms of 0.078 angstrom. The organic molecules, water and dimethyl sulfoxide solvent molecules are linked by N-H center dot center dot center dot O, O-H center dot center dot center dot O and O-H center dot center dot center dot S intermolecular hydrogen bonds, forming zigzag chains along the a axis. Intramolecular O-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonds also occur.